Turning the gaze to maize: The effects of maize kernels in straw as enrichment on exploration in pigs - K Kauselmann; L Schrader; B Glitz; E Gallmann; H Schrade; E Krause (Berliner und Münchener Tierärztliche Wochenschrift, 2020)
Tail biting is one of the biggest problems in pig production systems that causes animal welfare and economic problems. Therefore, tail docking is a widely used intervention to reduce tail biting. However, appropriate enrichment material that stimulates and increases exploration behaviour of pigs also reduces the prevalence and risk of tail biting. In 288 pigs with undocked tails we investigated whether the attractiveness of chopped straw (CS) as enrichment material can be further increased when maize kernels were added (CS+MK). Further, we examined whether a higher attractiveness is accompanied by reduced tail incidents. We used material dispensers equipped with ultra-high-frequency radio-frequency identification (UHFRFID) systems to record individual exploration times of the pigs to the offered enrichment materials. Furthermore, animals were scored thrice for tail length losses and tail injuries, i.e. after the rearing period, in the middle of the fattening period and at the end of the fattening period. Both rearing and fattening pigs had higher exploration durations when housed with CS+MK compared to CS (LME: rearing, P<0.001, fattening, P<0.05). Interestingly, enrichment materials not only remained interesting but were used even more from rearing to fattening. However, when CS+MK was offered pigs showed a higher prevalence for tail biting incidents in the rearing, but not in the fattening period, compared to CS (rearing GLMM, P<0.01). This may have resulted from competition for the more attractive enrichment material (CS+MK). An edible additive increased the interest for straw in pigs over long term but could not improve tail status.